이중언어교육에 대한 인식과 어려움: 다문화가족 특성화사업 직원을 중심으로 - 이순배; Soon Bae Yi; 김순환; Soon Hwan Kim (다문화와 평화, 2020)
이중언어교육에 책임을 갖는 센터, 학교 등의 전문가 모두 각 문화의 관습이 가진 중요성을 인식하고, 언어의 우세 및 소멸에 대해 민감성을 가지며 이중언어교육을 실행해야 할 의무를 진다(Paradis 외, 2012). 따라서 본 연구는 다문화가족지원센터 다문화가족 특성화사업 직원 중 방문교육지도사, 언어발달지도사, 이중언어코치, 운영지원 사무원으로 근무하며, 이중언어환경에 놓인 다문화가족 부모와 자녀들을 만나 이중언어교육을 실천하는 직원들을 연구참여자로 선정했다. 그리고 직원들의 이중언어교육에 대한 인식과 이중언어교육을 실천하는 가운데 나타나는 어려움에 대해 알아보았다. 연구참여자는 특성화사업 직원 5명으로, 이들의 이야기를 듣고, 다시 이야기하며 그들의 경험을 드러내고자 내러티브탐구를 실행했다. 그 결과 첫째, 다문화 가족지원센터 다문화 특화사업 직원을 대상으로 한 체계적인 교육프로그램을 제공할 필요가 있다. 연구참여자들은 자신이 이중언어교육을 실행하는 주체자임에도 불구하고 자신을 이중언어교육 실천가라고 인식하지 못했다. 이중언어교육에 대한 충분한 교육 없이 직무에 투입되면 정체성의 혼란을 겪기 쉽고, 자신의 전문성에 대해 의심하기 쉽다. 둘째, 다문화가족지원센터 직원에 대한 법적, 제도적 지원과 처우개선이 필요하다. 다문화가족 특성화사업 직원들은 직무과정에서 직무상의 어려움뿐만 아니라 열악한 근무환경과 낮은 급여로 인해 어려움을 경험했다. 센터 직원의 복지와 처우 개선은 직원들의 직무 향상으로 이어질 수 있을 것이다. This study investigated the perceptions of bilingual education and difficulties with its practice among the employees in charge of specialization projects for multicultural families at multicultural family support centers. These employees included visiting educational instructors, language development instructors, bilingual coaches, and staff that practice bilingual education by meeting parents and children in multicultural families in a bilingual environment. The subjects included five employees in charge of such specialization projects. A narrative inquiry was conducted to listen to their stories and reveal their experiences. The findings were as follows: first, there is a need to provide a systematic educational program to the employees in charge of multicultural specialization projects. The participants did not recognize themselves as practitioners of bilingual education even though they were the subjects providing the education. When they are placed in the field without enough education about bilingual, they can easily have confusion with their identity and develop doubts about their professionalism. Secondly, there should be legal and institutional support for employees at multicultural family support centers along with better conditions for them. The employees at such centers experience difficulties with inferior work environments and low salaries as well as with their duties in the job process. Contrary to their clients benefiting from the reciprocal environment at centers with various free services, the employees of the centers were in a rather inferior work environment and sacrificed their own welfare.